FELICIDADE CLANDESTINA IN FELICIDADE CLANDESTINA - Lispector, Clarice (2021)
Fonte: http://www.ufma.br/portalUFMA/arquivo/T6cNAlTP1F8ZRJN.pdf Tradução para escrita de sinais: Edneia de Oliveira Alves (PPGL/UFPB)Janaína Aguiar Peixoto(PPGL/UFPB)